1987
DOI: 10.1084/jem.166.5.1419
|View full text |Cite
|
Sign up to set email alerts
|

Activation and growth of colony-stimulating factor-dependent cell lines is cell cycle stage dependent.

Abstract: Hematopoietic cell development is regulated by a series of growth factors that are progressively restricted in their biological activity. IL-3 is a multi-lineage growth factor that supports the growth and differentiation of progenitor cells belonging to multiple lineages. However, the mechanism by which IL-3 induces proliferation and differentiation of these cells is not completely understood. In this report, we have used two IL-3-dependent cell lines, FDC-P1 (a myeloid progenitor) and F15.12 (a lymphoid proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Our finding, suggesting that GM-CSF stimulates GI to S-Dhase Droaession of HL-60 cells. Drovides the first data-on the egects of this cytokine 0; a synchronized human cell-line and extends results obtained with IL-3lGM-CSF-dependent mouse cell-lines and CSF-1dependent mouse peritoneal macrophages, where these hematokines also have been found to promote G, to S progression (Pluznik et al, 1984;Kelvin et al, 1986;London and McKearn, 1987;Hasthorpe et al, 1988;Tushinski and Stanley, 1985). We found that GM-CSF addition could be delayed for at least half of G, without compromising progression in the next cell cycle.…”
Section: A-supporting
confidence: 66%
“…Our finding, suggesting that GM-CSF stimulates GI to S-Dhase Droaession of HL-60 cells. Drovides the first data-on the egects of this cytokine 0; a synchronized human cell-line and extends results obtained with IL-3lGM-CSF-dependent mouse cell-lines and CSF-1dependent mouse peritoneal macrophages, where these hematokines also have been found to promote G, to S progression (Pluznik et al, 1984;Kelvin et al, 1986;London and McKearn, 1987;Hasthorpe et al, 1988;Tushinski and Stanley, 1985). We found that GM-CSF addition could be delayed for at least half of G, without compromising progression in the next cell cycle.…”
Section: A-supporting
confidence: 66%
“…There is also a decrease in RNA content as measured by acridine orange (AO) staining, another reported characteristic of the G0 state (Fig. 1C) (London and McKearn, 1987). …”
Section: Resultsmentioning
confidence: 94%
“…Murine myeloid progenitor cell line FDC-P1, which also expressed moderate levels of Nedd2 mRNA (Fig. 2) was chosen for the antisense studies using mouse Nedd2 cDNA expression constructs, because of its apoptosis response has been well characterized [29,30]. This cell line can be maintained with either GM-CSF or IL-3 and upon removal of the factor undergoes apoptosis within 1 2 days [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…2) was chosen for the antisense studies using mouse Nedd2 cDNA expression constructs, because of its apoptosis response has been well characterized [29,30]. This cell line can be maintained with either GM-CSF or IL-3 and upon removal of the factor undergoes apoptosis within 1 2 days [29,30]. FDC-P1 cells were transfected by lipofection with a mammalian expression vector (pCXN2), the vector carrying Nedd2 cDNA containing entire coding region in sense orientation (PCXN2-N2), or 5'-1.0 kb fragment of the Nedd2 cDNA in antisense orientation (pCXN2-N2AS).…”
Section: Resultsmentioning
confidence: 99%